Studying Organizational Change and Development: Challenges for Future Research - Pettigrew, Andrew; Woodman, Richard W.; Cameron, Kim S. (Academy of Management Journal, 2001)
This article presents several studies that examine organizational change. The authors note that certain issues should be addressed when examining the studies including an examination of the multiple contexts and levels of analysis in studying organizational change, the inclusion of time, history, process and action, the link between change processes and organizational performance, the investigation of international and cross-cultural comparisons, the study of receptivity, customization, sequenicng, pace and episodic versus continusous change and the partnership between scholars and practicioners in studying change. The author discuss how these issues are related to the concepts in the studies and note they research has not addressed these issues at this point in time.